The Fate of Incoming Stimuli during NREM Sleep is Determined by Spindles and the Phase of the Slow Oscillation - Schabus, Manuel; Dang-Vu, Thien Thanh; Heib, Dominik P.; Boly, Melanie; Desseilles, Martin; Vandewalle, Gilles; Schmidt, Christina; Albouy, Genevieve; Darsaud, Annabelle; Gais, Steffen; Degueldre, Christian; Balteau, Evelyne; et al. (Frontiers in Neurology, 2012)
The present study aimed at identifying the neurophysiological responses associated with auditory stimulation during non-rapid eye movement (NREM) sleep using simultaneous EEG/fMRI recordings. It was reported earlier that auditory stimuli produce bilateral activation in auditory cortex, thalamus, and caudate during both wakefulness and NREM-sleep. However, due to the spontaneous membrane potential fluctuations cortical responses may be highly variable during NREM. Here we now examine the modulation of cerebral responses to tones depending on the presence or absence of sleep spindles and the phase of the slow oscillation. Thirteen healthy young subjects were scanned successfully during stage 2-4 NREM sleep in the first half of the night in a 3T scanner. Subjects were not sleep-deprived and sounds were post-hoc classified according to (i) the presence of sleep spindles or (ii) the phase of the slow oscillation during (±300ms) tone delivery. These detected sounds were then entered as regressors of interest in fMRI analyses. Interestingly wake-like responses persisted during NREM sleep, except during present spindles (Dang-Vu et al., 2011) and the positive going phase of the slow oscillation during which responses became absent. While the phase of the slow oscillation did not alter brain responses in primary sensory cortex, it did modulate responses at higher cortical levels. In addition EEG analyses show a distinct N550 response to tones during the presence of spindles and suggest that in deep NREM sleep the brain is more responsive during the negative going slope of the slow oscillation. The presence of short temporal windows during which the brain is open to external stimuli is consistent with the fact that even during deep sleep meaningful events can be detected. Altogether, our results emphasize the notion that spontaneous fluctuations of brain activity profoundly modify brain responses to external information across all behavioural states, including deep NREM sleep